The child with a cleft palate - Backus, Ollie Lucy, 1908-1999; Michigan. University. Institute for human adjustment. Speech clinic; Michigan. University. Hospital. Dept. of oral surgery; Clancy, John Newman; Henry, Lucy Dell, 1896-; Kemper, John Willard, 1891- (Ann Arbor (Mich.) : University of Michigan press, 1943)
Boek over de problematiek van kinderen met een gespleten verhemelte.
Keywords: Palate -- Surgery; Speech -- Study and teaching